Active motility and chemotactic movement regulate the microbial early-colonization and biodiversity - Yan Wang; Ali Ebrahimi; Guowei Chen; Zi Zhang; Kun Zhu; Shane Franklin; Yan Jin; Ying Liu; Gang Wang (Geoderma)
Microbial dispersal and subsequent colonization of new niches are fundamental processes in microbial ecology, particularly in patchy environments like soil. However, the heterogeneity of soil pore spaces and the resulting fragmented aqueous habitats are known to significantly impede microbial dispersal rates and ranges. Despite this, the strategies microbes employ to overcome these abiotic constraints remain poorly understood. To address this, we developed a novel experimental system using porous ceramic surfaces to simulate hydrated soil environments, enabling direct quantification of early-stage bacterial colonization. Our findings reveal that distinct taxonomic and functional bacterial populations successfully colonized the porous ceramic surfaces, differing significantly from the original soil communities. Active motility and chemotaxis emerged as two key traits facilitating early-stage colonization. However, the advantages conferred by motility and chemotaxis were significantly reduced under drier soil conditions, typically at water contents below 25% (v/v). Under such conditions, non-motile bacteria relied on passive dispersal mechanisms or physical adhesion to colonize the porous surfaces. Furthermore, functional metagenomic profiling of the colonizing microbial populations uncovered a trade-off between growth and dispersal rates. This observed trade-off was incorporated into an agent-based model simulating microbial activity in soil, which explored how correlations between microbial functional genes influence community dynamics during early colonization. The simulations demonstrated that the growth-dispersal trade-off is crucial for enhancing and maintaining microbial diversity during colonization of new niches. Our study elucidates the key biophysical mechanisms driving microbial early-stage colonization dynamics from bulk soil to new environments, highlighting this process as a core ecological phenomenon in soil ecosystems.